2021
DOI: 10.3390/ijms221910678
|View full text |Cite
|
Sign up to set email alerts
|

PPAR-α Hypermethylation in the Hippocampus of Mice Exposed to Social Isolation Stress Is Associated with Enhanced Neuroinflammation and Aggressive Behavior

Abstract: Social behavioral changes, including social isolation or loneliness, increase the risk for stress-related disorders, such as major depressive disorder, posttraumatic stress disorder (PTSD), and suicide, which share a strong neuroinflammatory etiopathogenetic component. The peroxisome-proliferator activated receptor (PPAR)-α, a newly discovered target involved in emotional behavior regulation, is a ligand-activated nuclear receptor and a transcription factor that, following stimulation by endogenous or syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 71 publications
0
22
0
Order By: Relevance
“…As mentioned above, neural circuits that modulate aggressive behaviour also include the hippocampus and hypothalamus [ 121 , 122 , 123 , 124 , 125 ]. Specifically, atypical hippocampal anatomical asymmetries that disrupt prefrontal–hippocampal circuitry may result in emotion dysregulation with increased aggressiveness because hippocampal neurons have robust projections that originate from hippocampal CA1 and terminate in the orbital and medial frontal cortices [ 126 ].…”
Section: Neuroanatomical Basis Of Aggression In Humans and Rodents In...mentioning
confidence: 99%
“…As mentioned above, neural circuits that modulate aggressive behaviour also include the hippocampus and hypothalamus [ 121 , 122 , 123 , 124 , 125 ]. Specifically, atypical hippocampal anatomical asymmetries that disrupt prefrontal–hippocampal circuitry may result in emotion dysregulation with increased aggressiveness because hippocampal neurons have robust projections that originate from hippocampal CA1 and terminate in the orbital and medial frontal cortices [ 126 ].…”
Section: Neuroanatomical Basis Of Aggression In Humans and Rodents In...mentioning
confidence: 99%
“…Moreover, it has recently been shown that Nrf2 activation in microglia is associated with an improvement in dendritic spine morphology in stressed mice [ 118 ]. Finally, a study looking at hippocampal sections of mice stressed by social isolation supported a role of MeCP2 in modulating oxidative stress [ 119 ], which has already been seen in RTT [ 120 , 121 ]. This can be explained by the actions of MeCP2 on genes essential in antioxidant and radical scavenger pathways.…”
Section: Mecp2 and Stress-related Pathology: Focus On Depressionmentioning
confidence: 90%
“…The activation of PPAR-α receptor initiates a cascade of events that causes the suppression of pain and inflammation, including decreases in pro-inflammatory cytokines such as IL-1β and IL-6, and TNF-α [ 57 ]. Moreover, low levels of PPAR-α are also responsible of several pathological conditions, neurodegenerative diseases, and stress-related disorders [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, here we found that the effects of um-PEA were significantly inhibited by the administration of either AM281 (CB1 antagonist) or GW6471 (PPAR-α antagonist). As already mentioned, the reduction in or the absence of CB1 and PPAR-α could lead to neuroinflammation [ 66 , 74 , 75 , 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%